'In' Box. (Chronicle of Higher Education, 1982)
The article presents news briefs on issues related to selection of computer programmers, computers and the retirement of professors. Lawyer Charlotte Roederer suggests that college administrators should consider musicians in hiring computer programmers. About 25,000 Apple II personal computers are being planned by Apple Computer to donate to elementary and secondary schools if the U.S. Congress enacts special tax breaks being searched by the company. The reason of the Committee A of the American Association of University Professors for exempting faculty members from any uncapping of mandatory retirement is provided.